2021
DOI: 10.3390/cancers13133260
|View full text |Cite
|
Sign up to set email alerts
|

HPV Genotyping by Molecular Mapping of Tissue Samples in Vaginal Intraepithelial Neoplasia (VaIN) and Vaginal Squamous Cell Carcinoma (VaSCC)

Abstract: HPV genotypes were determined in 63 vaginal squamous intraepithelial neoplasia (VaIN) and 7 vaginal squamous cell carcinomas (VaSCC). Of these, 37 cases had VaIN alone, and 26 cases had both VaIN and cervical intraepithelial neoplasia (CIN) or condyloma. HPV typing was performed in scraped cells by Genosearch-31 (GS-31) and in the archived tissues by uniplex E6/E7 PCR. In a total of 49 VaIN1, 17 VaIN2/3, and 7 VaSCC tissues, the prevalence of HPV was 91.2% in VaIN (VaIN1: 87.8%, VaIN2/3: 100%) and 85.7% in VaS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…A previous study from our group showed that at least one HR-HPV or pHR-HPV can be detected in CIN2 or CIN3 FFPE tissues, 37 which is consistent with the present results (HPV-positive rate was 100% in CIN2 tissues). One case (case no.…”
Section: Discussionsupporting
confidence: 93%
“…A previous study from our group showed that at least one HR-HPV or pHR-HPV can be detected in CIN2 or CIN3 FFPE tissues, 37 which is consistent with the present results (HPV-positive rate was 100% in CIN2 tissues). One case (case no.…”
Section: Discussionsupporting
confidence: 93%
“…As especially HPV 16 and HPV 31 were found to be highly associated with high-grade VaIN, it is advisable to be particularly attentive for signs of VaIN among patients tested positive for these hrHPV subtypes [ 53 ]. However, to add another degree of complexity, recent data suggests that concomitant CIN and VaIN in the same patient develop independently, since in the great majority of cases different hrHPV types were identified within the cervical and vaginal lesions [ 54 ]. Both patients who were diagnosed with VaIN 3 in our study were HPV 16 positive and did not have any cervical abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the prevalence of HPV58 in patients with CIN. In most instances, the differing distribution of HPV types between the vagina and cervix suggests that VaIN and CIN develop independently of each other [22]. The results indicated the close association of high-risk HPV infection with the occurrence of concurrent VaIN and CIN.…”
Section: Prevalence and Clinical Data Distributionmentioning
confidence: 85%